The Oxford Worries about Labour Scale: women's experience and measurement characteristics of a measure of maternal concern about labour and birth. - Redshaw, M; Martin, C; Rowe, R; Hockley, C (2009)
This study describes the measurement characteristics of a short (9-item) multi-dimensional measure of worry about labour and birth, the Oxford Worries about Labour Scale (OWLS-9), and its use in a large-scale study of women's experience of care. The data utilised were from 2960 women who participated in a national survey of a random sample of women who had recently given birth in England. Exploratory factor analysis revealed three sub-scales within the instrument assessing specific concerns about labour pain and distress, pre-labour uncertainty and interventions. The characteristics of each sub-scale revealed good divergent and discriminant validity. Further, the labour and distress subscale score was found to be significantly associated with both self-reported 'baby blues' and self-reported postnatal depression. The study findings suggest that the three sub-scales embedded can be utilised or the OWLS-9 employed as a full-scale instrument. Used antenatally, the OWLS-9 and OWLS sub-scales may offer a relevant and clinically useful measure of worry about labour and birth. Limitations of the study are discussed and the direction of future research indicated.